Pelatihan Produksi Pupuk Organik Padat dan Pengelolaan Koperasi Berkah Abadi Jaya di Sentra Tanaman Cabai Lubuk Cuik - Ilmi, Ilmi; Suherman, Suherman; Irmansyah, Teuku; Dilham, Ami; Eulis Diana, Vivi; Harahap, Muchsin (Universitas Medan Area, 2024)
The chili farming center in Lubuk Cuik Village, Batu Bara Regency, is the second largest after Karo Regency, with a total area of 1,092 hectares. The challenges faced by members of the Berkah Abadi Jaya Cooperative include declining soil fertility, low productivity, and high fertilizer costs, affecting farmers' profits. To address these issues, training on compost production and cooperative management was provided. Initially, members were trained to make compost from agricultural waste (leaves) and animal manure (KOHE). These materials were sprayed with Yanysis technology to accelerate the composting process. Participants were also trained to operate compost shredders to reduce leaf size. Solid organic fertilizer (POP), made from a mixture of leaf compost, KOHE, and humus soil, was applied to a chili plot and compared to chemical fertilizers. The results showed that cooperative members were able to independently produce POP. The composting time was reduced from 1-3 months to 2 weeks, while the plant height, number of leaves, and chili fruits were similar. Additionally, cooperative members gained a good understanding of cooperative business management, decision-making, and business diversification.